Effects of Chinese Herbal Medicine Combined with He-Ne Laser on Lipoperoxide and Superoxide Dismutase in Chloasma Patients - 吴艳华 李其林 杨秀文 (Journal of traditional Chinese medicine, 2009)
Objective： To observe the effects of Chinese decoction and ligustrazin hydrochloride injection combined with He-Ne laser on lipoperoxide （LPO） and Superoxide dismutase （SOD） in patients with chloasma. Methods： 90 cases of chloasma were randomly divided into the following two groups： a treatment group （of 54 cases） treated by a self-prepared prescription for toning the kidneys and relieving the depressed liver to remove blood stasis, ligustrazin hydrochloricde injection and He-Ne laser therapy, and a control group （of 36 cases） treated with oral administration of Vitamin E and Vitamin C plus external application of 20% Azelaic acid cream. Results： The total effective rate in the treatment group was 79.6%, which was significantly higher than that of the control group （P〈0.05）. After treatment, the LPO level in the treatment group was significantly lowered （P〈0.01）, and the SOD level was significantly elevated （P〈0.05）. Conclusion： The therapeutic methods adopted in the treatment group may show the action of antioxidation, providing good clinical effects for treating chloasma.